The optimization of bagasse leaf-based porous carbon-tin oxide organic capacitor using Taguchi method - Setyanto, Nasir Widha; Sugiono, Sugiono; Irawan, Yudy Surya; Nugroho, Willy Satrio; Wardana, I Nyoman Gede (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the carbon-based organic capacitors, derived from bagasse leaves from the Kebon Agung sugar factory, Malang, Jawa Timur, serving as a sustainable precursor material. The challenge of optimizing the performance of bagasse leaf-based organic capacitors has been a significant barrier in advancing sustainable electronic components. This study aims to develop a quality framework for synthesizing these capacitors by systematically optimizing the parameters using the Taguchi method. Traditional methods often lead to inconsistent performance and high variability, making it difficult to achieve reliable results. By applying the Taguchi orthogonal array, this study identified key factors and optimal levels, effectively reducing experimental efforts while ensuring robust performance. The carbonization of bagasse leaves was conducted using direct combustion with thinner and 70% methanol as liquid burners. Capacitance tests revealed stable values ranging from 0.8897 nF to 0.9281 nF across trials, demonstrating consistent and reproducible behavior. Thermal noise evaluation showed slight temperature variations (69.01°C to 72.01°C), indicating the influence of temperature on electron mobility within the dielectric materials. The systematic approach of the Taguchi method minimized variability and enhanced the capacitors' reliability under varying thermal conditions. The method's focus on robustness and quality control ensured consistent capacitance values and improved overall capacitor performance. Compared to traditional methods, the Taguchi method facilitated a thorough exploration of the design space with fewer experiments. This study underscores the importance of systematic optimization in capacitor design, offering a reliable pathway to integrate sustainable materials into advanced electronic components. The results provide valuable insights into the effects of different parameters on performance metrics, enhancing the development of high-quality organic capacitors